Coinfusion of low-dose GLP-1 and glucagon in man results in a reduction in food intake - Cegla,J; Troke,RC; Jones,B; Tharakan,G; Kenkre,J; McCullough,KA; Lim,CT; Parvizi,N; Hussein,M; Chambers,ES; Minnion,J; Cuenco,J; et al. (Diabetes, 2014)
Obesity is a growing epidemic, and current medical therapies have proven inadequate. Endogenous satiety hormones provide an attractive target for the development of drugs that aim to cause effective weight loss with minimal side effects. Both glucagon and GLP-1 reduce appetite and cause weight loss. Additionally, glucagon increases energy expenditure. We hypothesized that the combination of both peptides, administered at doses that are individually subanorectic, would reduce appetite, while GLP-1 would protect against the hyperglycemic effect of glucagon. In this double-blind crossover study, subanorectic doses of each peptide alone, both peptides in combination, or placebo was infused into 13 human volunteers for 120 min. An ad libitum meal was provided after 90 min, and calorie intake determined. Resting energy expenditure was measured by indirect calorimetry at baseline and during infusion. Glucagon or GLP-1, given individually at subanorectic doses, did not significantly reduce food intake. Coinfusion at the same doses led to a significant reduction in food intake of 13%. Furthermore, the addition of GLP-1 protected against glucagon-induced hyperglycemia, and an increase in energy expenditure of 53 kcal/day was seen on coinfusion. These observations support the concept of GLP-1 and glucagon dual agonism as a possible treatment for obesity and diabetes.